Comparison of noise reduction in different hearing aids using malay-hearing-in-noise-test - Nor, Anisah Mohd (Universiti Sains Malaysia, 2016)
This was a study to determine and compare the Malay-Hearing-In-Noise (MyHINT} scores of noise reduction function in different hearing aids. Noise reduction was a technology in hearing aids that help to amplify meaningful sounds such as speech while reducing the effect of background noise. Ten adult subjects from Audiology Clinic, Hospital USM and Audiology Laboratory, PPSK USM age more than 18 years old with mild to severe sensorineural hearing loss that fulfilled the inclusion criteria were included in this study. Subjects were tested using two different hearing aids with the noise reduction was activated and deactivated in two different test condition. The MyHINT consisted 12 list of short sentences and each lists contain 20 sentences. The stimuli were delivered through speaker and subjects were required to repeat the sentences that they heard with the hearing aid on. The finding from this study showed that there was no significant difference (p>0.05) in noise reduction in different hearing aids when using MyHINT in the presence of background noise. Surprisingly, the scores for MyHINT was better when the noise reduction was switched off, hence it cannot conclude whether this test was suitable to be used as a tool to determine the benefit of noise reduction in clinical setting. Whereas, the findings from this study also indicated that noise reduction did provide some benefits to HA wearer even though the advantages of noise reduction may not significantly be seen in all subject scores.